The Effect of Aging Under Loading on the Phase Transformation Behavior of Near-Equiatomic NiTi Shape Memory Alloy - Kucukyildirim, Bedri Onur (SPRINGER, 2015)
The phase transformation temperature of nickel titanium (NiTi) shape memory alloy (SMA), which is commonly used in biomaterial fields, is strongly influenced by aging heat treatments. In this study, we apply a new aging heat treatment under loading conditions to near-equiatomic NiTi SMA wires to investigate its effect on phase transformation temperatures. We determine changes in the phase transformation temperatures via differential scanning calorimetry measurements. We analyze transformation temperatures, hysteresis properties, and enthalpy changes and discuss significant results with the help of micrographs. Moreover, we evaluate our results using two-way analysis of variance, axiomatic design methods, and customary analysis in order to make reliable inferences. We observe a significant difference between first and second heating-cooling cycle results for NiTi SMA samples on the basis of austenitic transformation temperatures. Consequently, we are able to theorize correlations between design parameters and functional requirements.
Keywords: aging; axiomatic design; differential scanning calorimetry (DSC); phase transformations; shape memory alloys; MARTENSITIC-TRANSFORMATION; COMBUSTION SYNTHESIS; TEMPERATURE; CU; PARAMETERS; EVOLUTION; WIRES; Materials Science